The Australian Preferential Tariff Regime - Lippoldt, Douglas C.. (OECD Trade Policy Papers, 2006)
The purpose of this paper is to consider the preferential trade arrangements available to developing countries exporting into the Australian market. The paper opens with an overview of these arrangements, followed by a detailed statistical review. It then moves to examine several topics of particular interest in the discussion of Australian preferences. A simulation of the welfare impacts of preference erosion is then presented, followed by some brief concluding remarks